Head-to-Head: Recombinant Human Prourokinase Versus Intravenous Thrombolytics in Acute Ischemic Stroke Within 4.5 Hours – A Systematic Review and Network Meta-Analysis of Randomized Clinical Trials - Muhammad Hassan Waseem MBBS; Zain ul Abideen MBBS; Areeba Shoaib MBBS; Muhammad Osama MBBS; Muhammad Abdullah Ali MBBS; Sania Aimen MBBS; Muhammad Wajih Ansari MD; Rowaid Ahmad MD; Muhammad Arslan Tariq MD; Ameer Haider Cheema MD; Aleeza Afzal MBBS; Pawan Kumar Thada MBBS (Clinical and Applied Thrombosis/Hemostasis)
Background Intravenous thrombolytics are essential for achieving timely reperfusion in acute ischemic stroke (AIS), with alteplase historically serving as the standard of care. Emerging alternatives like recombinant human prourokinase (rhPro-UK), reteplase, and tenecteplase offer potential improvements in efficacy, safety, and convenience, necessitating a comparative analysis. Methods Electronic databases, including PubMed, ScienceDirect, and Cochrane Central, were comprehensively searched from inception till December 2024 for relevant studies. A frequentist network meta-analysis was performed using R software version 4.2.3, and the “netmeta” package was employed. Alteplase 0.9 mg served as the reference group, with P-scores employed to determine the relative rankings of various interventions. The risk of publication bias was evaluated through funnel plots and Egger's regression test. Results Eighteen trials with 12,950 participants were included in the final analysis. Compared to alteplase 0.9 mg, excellent functional outcome (mRS 0-1) was significantly improved by Reteplase 18 + 18 mg (RR = 1.13, p < 0.01) and Tenecteplase (TNK) 0.25 mg (RR = 1.05, p < 0.01). For a good functional outcome (mRS 0-2), Reteplase 18 + 18 mg (RR = 1.06, p < 0.01) and TNK 0.32 mg (RR = 1.30, p < 0.01) were significantly more effective than alteplase. Safety outcomes, symptomatic intracranial hemorrhage (sICH), and mortality were not significantly different between alteplase and other thrombolytics. According to P-scores, Reteplase 18 + 18 mg ranked the best for excellent functional outcome (P-score = 0.89) and TNK 0.32 mg for good functional outcome (P-score = 0.99), while rhPro-UK 35 mg ranked the best for sICH (P-score = 0.89). Conclusion Reteplase 18 + 18 mg and TNK 0.32 mg demonstrated superior functional outcomes compared to alteplase, while rhPro-UK 35 mg showed the best safety profile with the lowest sICH risk.